Simultaneously improving fracture toughness and impact resistance of the rapid-curing CFRP via insert with MAM/EP resin film. (April 2023) - Liu, Yuhang; Min, Wei; Qi, Liangliang; Muhuo, Yu; Sun, Zeyu
In this research, a resin film of the MAM/EP blend curing system containing the triblock copolymer polymethyl methacrylate- b -poly-n-butyl acrylate- b -polymethyl methacrylate (MAM) was prepared. Such resin film was inserted into the interlaminar of rapid-curing composites to simultaneously improve both mode I, mode II fracture toughness and impact resistance. Both the Mode I and Mode II interlaminar fracture toughness of the composites were carefully investigated as a function of MAM content of the MAM/EP resin film (0, 20 and 40 phr@50 μm). A maximum improvement up to 109% and 70.2% on Mode I and Mode II fracture toughness, respectively was obtained with the introduction of the 40 phr@50 μm compared to the laminates with the introduction of the 0 phr@50 μm. Analysis of the fracture surfaces of the laminates elucidated that the distinctive improvement of the interlaminar fracture toughness could be attributed to the characteristic interlaminar structures of MAM in epoxy resin by self-assembly. The interleaved laminates also displayed an increase of 26.7% for the compression after impact (CAI) properties, and showed excellent impact resistance. The interlaminar shear strength (ILSS) of the composite was thereafter explored, which indicated slight enhancements to the strengths.